2022
DOI: 10.1177/03635465221083995
|View full text |Cite
|
Sign up to set email alerts
|

Stretch-Induced Healing of Injured Muscles Is Associated With Myogenesis and Decreased Fibrosis

Abstract: Background: Alghouth therapeutic stretching exercise has been applied to accelerate the healing of injured skeletal muscles, mechanisms behind the mechanical stretch-induced muscle recovery remain unclear. Purpose: To examine stretch-associated antifibrotic and myogenic responses in injured muscles and to evaluate the feasibility of the ultrasonic Nakagami parametric index (NPI) in assessing muscle morphology during recovery. Study Design: Controlled laboratory study. Methods: Skeletal muscle fibrosis was indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…The fibrotic scar produced is important for tissue integrity during the early phases of muscle healing; however, its presence in later stages has a detrimental effect on muscle function [ 38 ]. Therefore, the development of therapies aimed at reducing muscle fibrosis may be promising, such as stretching exercises [ 42 , 43 , 44 ] or the use of drugs targeting pro-fibrotic cytokines [ 45 , 46 , 47 ] that have been shown to improve muscle healing by reducing muscle fibrosis and increasing myogenesis. Several studies have shown that physical exercise and stretching have an effect on mesenchymal stem cells (MSCs) through mechanotransduction, converting the mechanical loading into different cellular responses that have an impact on improving muscle regeneration [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fibrotic scar produced is important for tissue integrity during the early phases of muscle healing; however, its presence in later stages has a detrimental effect on muscle function [ 38 ]. Therefore, the development of therapies aimed at reducing muscle fibrosis may be promising, such as stretching exercises [ 42 , 43 , 44 ] or the use of drugs targeting pro-fibrotic cytokines [ 45 , 46 , 47 ] that have been shown to improve muscle healing by reducing muscle fibrosis and increasing myogenesis. Several studies have shown that physical exercise and stretching have an effect on mesenchymal stem cells (MSCs) through mechanotransduction, converting the mechanical loading into different cellular responses that have an impact on improving muscle regeneration [ 48 ].…”
Section: Discussionmentioning
confidence: 99%